Impact of Cumulative Fluid Balance During Continuous Renal Replacement Therapy on Mortality in Patients With Septic Acute Kidney Injury: A Retrospective Cohort Study - Lin, Jin; Zhuang, Hai Zhou; Zhi, De Yuan; Qi, Zhili; Bai, Jing; Dong, Lei; Liu, Shuai; Duan, Meili (Frontiers in Medicine, 2021)
Background: Clinicians often use continuous renal replacement therapy (CRRT) for fluid management of patients with septic acute kidney injury (AKI), however, there is a lack of knowledge about changes in fluid balance (FB) on CRRT and its association with outcomes in patients with septic AKI. Objective: To determine the association of cumulative fluid balance during treatment with all-cause 28-day mortality in septic AKI patients who require CRRT. Methods: This retrospective observational study examined patients who received CRRT due to septic AKI in mixed intensive care units (ICUs) of a tertiary teaching hospital between January 2015 and December 2018. Patients were divided into 3 groups — negative FB, even FB, and positive FB — based on cumulative FB (CFB) during CRRT. The primary outcome was 28-day all-cause mortality. Results: We examined 227 eligible patients and the mean age was 62.4 ± 18.3 years. The even FB group had a significantly lower 28-day mortality rate (43.0%, p=0.007) than the positive FB group (72.7%) and the negative FB group (54.8%). Unadjusted and adjusted Cox regression models indicated that the positive FB group had an increased risk for 28-day all-cause mortality relative to the even FB group. A restricted cubic splines model indicated a J-shaped association between CFB and 28-day all-cause mortality in the unadjusted model. Conclusion: Among critically ill patients with septic AKI requiring CRRT, those with positive FB compared to even FB had a higher mortality rate.